International business strategy - Verbeke, Alain; Lee, Ian (Cambridge : Cambridge University Press, 2022)
Now in its third edition, this core textbook for advanced undergraduate, graduate, and postgraduate students combines analytical rigour and managerial insight on the functioning and strategy of large multinational enterprises (MNEs). Verbeke and Lee develop an original conceptual model that supports student learning by providing an integrated perspective, rooted in theory and practice. The discussion also includes unique commentaries on seventy-four seminal articles published in the Harvard Business Review, the Sloan Management Review, and the California Management Review over the past four decades, demonstrating how the key insights can be applied to real businesses engaged in international expansion programmes, especially as they venture into high-distance markets. This third edition has been thoroughly updated and features new sections on multinational entrepreneurship, strategic challenges in the new economy, and international business strategy during globally disruptive events, including the COVID-19 pandemic. Students will benefit from updated case studies, improved learning features, and a wide range of online resources.
Title from publisher's bibliographic system (viewed on 02 Sep 2021).
Keywords: elektronické knihy; electronic books; International business enterprises -- Management; Strategic planning -- Case studies; Strategic planning; International business enterprises -- Management -- Case studies